Mengatasi Dampak Media Sosial Youtube Bagi Perkembangan Kognitif Anak Usia Dini - Yunia, Vera (Universitas Nusa Cendana, 2022)
Early childhood is a child who is in the age range of 0-8 years, where currently all aspects of child development must be stimulated, especially children's cognitive development. Physical, social and cognitive development of a child will develop very rapidly when the child is 1-2 years old. The very rapid development of technology at this time makes everything easier, especially the means of developing cognitive aspects of early childhood through the medium of YouTube. The purpose of this study is to explain how to overcome the impact of YouTube social media for early childhood. This study uses a qualitative field method with this type of research. This research is a qualitative research that is library research which uses books and other literatures as the main object. The provision of social media to children must also be accompanied by parents, because YouTube has positive and negative impacts that can affect children's cognitive development. Keywords : social media, intelligence development, early childhood